2017
DOI: 10.1186/s12877-017-0539-8
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric versus traditional resistance exercise for older adult fallers in the community: a randomized trial within a multi-component fall reduction program

Abstract: BackgroundAddressing muscle deficits within a multi-component exercise fall reduction program is a priority, especially for the highest risk older adults, i.e., those who have fallen previously. Eccentric resistance exercise with its high-force producing potential, at a low energetic cost, may be ideally-suited to address muscle impairments in this population. The purpose of this study was to compare the effects of resistance exercise via negative, eccentrically-induced, work (RENEW) versus traditional (TRAD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 61 publications
3
48
0
5
Order By: Relevance
“…Nevertheless, the repeated bout effect, which includes neural and structural adaptations, protects against muscle damages from subsequent ECC bouts . Thus, an ECC cycling program can be achieved without undue DOMS provided a progressive ramping protocol is followed …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the repeated bout effect, which includes neural and structural adaptations, protects against muscle damages from subsequent ECC bouts . Thus, an ECC cycling program can be achieved without undue DOMS provided a progressive ramping protocol is followed …”
Section: Introductionmentioning
confidence: 99%
“…9,10 Thus, an ECC cycling program can be achieved without undue DOMS provided a progressive ramping protocol is followed. 4,11 Although the impact of ECC training on lean mass (LM) has been extensively studied, the findings are too varied to clearly affirm the superiority of ECC training. [11][12][13][14] Recent meta-analyses demonstrated that when matched for load or work, changes between ECC and CON training were found similar in regard to muscle hypertrophy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A specially designed training system (Eccentron; Baltimore Therapeutic Equipment, Hanover, MD, USA) was used to perform ECT ( Figure 1A) [15]. The knee extensor and ankle plantar flexor muscles were trained using ECT by negatively resisting the Eccentron pedals which are cross-driven at equal speeds using the leg muscles.…”
Section: Methodsmentioning
confidence: 99%
“…These authors have shown that in patients with severe COPD, 10 weeks of EET led to increases in muscle strength and hypertrophy, at progressively lower levels of perceived fatigue and dyspnea. Similar applications of EET have led to increased lower limb strength in patients with spinal cord injuries [4] and EET is as successful as traditional rehabilitation when addressing fall risks in elderly subjects [5]. The physiological adaptation stimulated by EET in clinical populations has the potential to extend to healthy subjects and in particular to competitive sport, where the continuous search for training methods to enhance performance is paramount.…”
Section: Improving Muscle Strength Using Eccentric Ergometry Trainingmentioning
confidence: 99%